2015
DOI: 10.1016/j.ebiom.2015.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Cancer Prevention: From Mammogram Screening to Identification of BRCA1 / 2 Mutation Carriers in Underserved Populations

Abstract: BackgroundThe US Preventative Service Task Force recommends that physicians perform a genetic risk assessment to identify women at risk for BRCA1/2 mutations associated with hereditary breast and ovarian cancer (HBOC) syndrome. However, outcomes data after a diagnosis of HBOC syndrome especially in diverse populations, are minimal. Here we asked if genetic screening of high-risk underserved women identified in the mammogram population reduces cancer incidence.MethodsWe evaluated 61,924 underserved women at scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 27 publications
(34 reference statements)
0
24
2
Order By: Relevance
“…Genetic counselors focusing on cancer genetics may have more direct exposure to the challenges hereditary cancer‐related PBS would exacerbate as they may frequently discuss BRCA‐related and Lynch syndrome indications with patients and providers given prevalence of these conditions; such exposure may influence perception of the ability to overcome challenges PBS may present compared to peers in other specialties. Additionally, cancer‐specific experience may confer increased readiness in PBS implementation as several cancer‐focused genetic counselors have reported results from broad screening protocols (Hampel, 2018; Robinson et al., 2015; Ross, Pirzadeh‐Miller, Lahiri, & Gemmell, 2019) that may be able to be replicated. Alternatively, genetic counselors in non‐medical settings in this study may have indicated greater support of PBS as they often are not providing direct patient care and do not directly feel professional burdens from the high demand on patient‐facing genetic counselors, including overbooked patient clinics and rigors of clinical documentation.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic counselors focusing on cancer genetics may have more direct exposure to the challenges hereditary cancer‐related PBS would exacerbate as they may frequently discuss BRCA‐related and Lynch syndrome indications with patients and providers given prevalence of these conditions; such exposure may influence perception of the ability to overcome challenges PBS may present compared to peers in other specialties. Additionally, cancer‐specific experience may confer increased readiness in PBS implementation as several cancer‐focused genetic counselors have reported results from broad screening protocols (Hampel, 2018; Robinson et al., 2015; Ross, Pirzadeh‐Miller, Lahiri, & Gemmell, 2019) that may be able to be replicated. Alternatively, genetic counselors in non‐medical settings in this study may have indicated greater support of PBS as they often are not providing direct patient care and do not directly feel professional burdens from the high demand on patient‐facing genetic counselors, including overbooked patient clinics and rigors of clinical documentation.…”
Section: Discussionmentioning
confidence: 99%
“…Although the offer and availability of cancer risk reduction strategies, genetic testing, genetic counselling and surveillance and treatment services differs across Western societies as per the different health care systems, inequality trends in use of those services appears common (Mehta 2005, Allford et al 2014, Daly & Olopade 2015. Among diverse patient populations, ethnic minority women, black women in particular, are visibly under-represented in who accesses the various cancer genetics services, including in uptake of interventions to reduce risk of developing breast and ovarian cancer (Armstrong et al 2005, Mehta 2005, Salant et al 2006, Halbert et al 2006, 2010, Kinney et al 2006, Ellington et al 2007, Bradbury et al 2008, Allford et al 2014, Robinson et al 2015, Lynce et al 2015, Underhill et al 2016, Cragun et al 2017, Jones et al 2017.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In this issue of EBioMedicine , Robinson et al ( Robinson et al, 2015 ) are to be commended for addressing interesting and important questions in clinical genetics that include population-level screening in underserved populations and the rate of adherence to risk reducing surgery recommendations. Using a predictive model of cancer reduction in patients with hereditary breast and ovarian cancer (HBOC) the authors estimated an 8.8% reduction in breast and ovarian cancer in the underserved group of mutation carriers compared to a 57% reduction in breast cancer and 51% reduction in ovarian cancer in an insured reference population with similar genetic risk.…”
mentioning
confidence: 99%
“…Expanding our awareness of additional factors that may influence use of genetic services and adherence to NCCN recommendations among underserved women at high risk for HBOC is a critical next step. Even with navigation for genetic services, half of the women from the safety net hospitals did not attend a scheduled appointment ( Robinson et al, 2015 ). Prior research denotes potential cultural, historical and attitudinal concerns as patient deterrents to genetic testing.…”
mentioning
confidence: 99%